Organic / inorganic composite anti-ultraviolet polyamide 66 fiber master batch, preparation method thereof and functional fiber
By adding organic/inorganic composite anti-UV nanomaterials, fluorescent whitening agents and dispersants during the melt blending and extrusion process of polyamide 66 resin, an organic/inorganic composite anti-UV polyamide 66 fiber masterbatch was prepared, which solved the problem of insufficient thermal stability of functional additives and powder dispersion, and achieved high-strength, fine fibers and fiber preparation with good UV resistance.
Patent Information
- Application Number
- CN202411712687.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
In the existing masterbatch blending and modification technology, the thermal stability of the functional additives is insufficient and the powder dispersion is poor, which leads to poor spinning properties during spinning, making it difficult to spin high-strength or fine fibers, and there is also a problem of color difference.
During the melt blending and extrusion process of polyamide 66 resin, organic anti-ultraviolet absorber, inorganic anti-ultraviolet absorber, fluorescent whitening agent and dispersant are added to prepare organic/inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch to improve the compatibility and dispersion of functional powders and resins.
The prepared fibers have good UV resistance, high strength, fineness, soft luster, soft feel and comfort, and are suitable for high-end clothing and clothing fabrics.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch and a preparation method thereof and functional fibers. Background Art
[0002] Ultraviolet rays (UV) contained in sunlight can cause damage to human health, the ecological environment and material structures. According to different wavelengths, ultraviolet rays can be divided into short-wave ultraviolet rays (UVC, 200-280 nm), medium-wave ultraviolet rays (UVB, 280-320 nm) and long-wave ultraviolet rays (UVA, 320-400 nm). Among them, UVC will be absorbed by the ozone layer, while UVB and UVA can break through the ozone layer to reach the earth's surface. UVB is very destructive to polymer materials and will cause the generation of free radicals, thereby destroying the internal binding energy of the polymer and reducing its mechanical properties. UVA is very harmful to the human body. It can penetrate into the human dermis, destroy the elastic fibers of the skin, cause skin aging, and in severe cases can also cause skin cancer. It has become a major health problem today.
[0003] Therefore, in order to solve the above problems, many anti-ultraviolet absorbers have been developed on the market, mainly including inorganic anti-ultraviolet absorbers and organic ultraviolet absorbers. Inorganic anti-ultraviolet absorbers mainly include rare earth oxides such as cerium oxide, yttrium oxide, samarium oxide, and gadolinium oxide, and inorganic oxides such as silicon dioxide and iron oxide; organic anti-ultraviolet absorbers mainly include benzophenones, salicylic acid, o-aminobenzophenones, triazines, polymeric hindered amines, methylene bis-benzotriazolyl tetramethylbutylphenol, etc. Organic ultraviolet absorbers can absorb ultraviolet rays and convert themselves into a high-energy state, release the absorbed energy in the form of heat, and then return to a state where ultraviolet light can be absorbed; while inorganic ultraviolet absorbers shield ultraviolet rays by absorption, scattering, refraction, etc.
[0004] The preparation technologies of anti-ultraviolet functional products include masterbatch blending and modification technology, fiber cross-section profiling technology, composite spinning technology, and post-finishing technology. In recent years, the preparation methods of anti-ultraviolet fabrics have mostly focused on post-finishing methods. Although they are easy to mass-produce and cheap, the fabrics feel hard and have poor durability. The masterbatch blending and modification technology is to add functional masterbatches online during spinning. The functional particles in the masterbatch are heated and melted and blended with nylon 66 resin to make them evenly dispersed in the polymer to produce functional fibers. The anti-ultraviolet fiber prepared by masterbatch blending and modification technology has a short process flow, is energy-saving and environmentally friendly, has a simple and easy-to-operate method, and has excellent fabric durability and washability. The type and content of the masterbatch can be flexibly changed according to needs, and is suitable for the functional requirements of various ultraviolet protection grade fibers and fabrics. However, the functional masterbatch added by the current masterbatch blending modification technology has the following main problems: 1) The functional additives in the masterbatch have insufficient thermal stability and are difficult to meet the processing temperature of nylon 66 spinning; 2) The powder added to the masterbatch has poor dispersibility and large particle size, resulting in poor spinnability during spinning and difficulty in spinning high-strength or fine-denier fibers; 3) The addition of functional powders causes color differences in the spun fibers, such as yellowing or whitening of the fibers. In view of the processing characteristics of polyamide 66 resin, such as high processing temperature, high processing viscosity, and narrow modulation window of spinning process parameters, it is particularly important to prepare functional powders that meet the use requirements and screen special functional additives to improve the compatibility and dispersibility of functional powders with resins. Summary of the invention
[0005] The purpose of the present invention is to provide an organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, a preparation method thereof and anti-ultraviolet fiber. The present invention prepares the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch by adding an organic anti-ultraviolet absorber and an inorganic anti-ultraviolet absorber, a fluorescent brightener and a dispersant during the melt blending and extrusion of polyamide 66 resin. The fiber and fabric made of the masterbatch have the anti-ultraviolet function and also have higher strength, finer fineness, soft gloss, soft feel and comfort.
[0006] In a first aspect, the present invention provides an organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, which is made of the following raw materials in parts by weight: 50-85 parts of polyamide 66 resin; 10-45 parts of organic / inorganic composite anti-ultraviolet nanomaterials; 0.5-10 parts of fluorescent whitening agent; Dispersant 0.2-5.0 parts; The organic / inorganic composite anti-ultraviolet nano material is made of an inorganic anti-ultraviolet material, a coupling agent and an organic ultraviolet absorber.
[0007] Specifically, the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch is made of the following raw materials in parts by weight: 50-76 parts of polyamide 66 resin; 20-40 parts of organic / inorganic composite anti-ultraviolet nanomaterials; 1.5-5.0 parts of fluorescent whitening agent; Dispersant 2.5-5.0 parts; The organic / inorganic composite anti-ultraviolet nano material is made of an inorganic anti-ultraviolet material, a coupling agent and an organic ultraviolet absorber.
[0008] More specifically, the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch is any one of the following: (1) In parts by weight, it is made from the following raw materials: 60 parts of polyamide 66 resin; 35 parts of organic / inorganic composite anti-ultraviolet nanomaterials; 2.0 parts of fluorescent brightener; 3.0 parts of dispersant; The organic / inorganic composite anti-ultraviolet nanomaterial is made of an inorganic anti-ultraviolet material, a coupling agent and an organic ultraviolet absorber; (2) In parts by weight, it is made from the following raw materials: 50 parts of polyamide 66 resin; 40 parts of organic / inorganic composite anti-ultraviolet nanomaterials; 5.0 parts of fluorescent whitening agent; Dispersant 5.0 parts; The organic / inorganic composite anti-ultraviolet nanomaterial is made of an inorganic anti-ultraviolet material, a coupling agent and an organic ultraviolet absorber; (3) In parts by weight, it is made from the following raw materials: 76 parts of polyamide 66 resin; 20 parts of organic / inorganic composite anti-ultraviolet nanomaterials; 1.5 parts of fluorescent brightener; 2.5 parts of dispersant; The organic / inorganic composite anti-ultraviolet nano material is made of an inorganic anti-ultraviolet material, a coupling agent and an organic ultraviolet absorber.
[0009] In the above-mentioned organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, the fluorescent whitening agent is selected from one or more of 3-(4-chlorophenyl)-1-(4-phenylsulfonic acid) pyrazoline, 2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene, and 4-(2-benzoxazolyl)-4'-(5-methyl-2-benzoxazolyl) diphenylethylene.
[0010] In the above-mentioned organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, the inorganic anti-ultraviolet material is selected from one or more of titanium dioxide, cerium dioxide, and zinc dioxide, and the particle size is 100 to 800 nm, such as 400 nm; The organic ultraviolet absorber is selected from one or more of 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazine-4-one, 2-[4-(4,6-diphenyl-1,3,5-triazine-2-yl)-3-hydroxyphenoxy]ethyl-2-ethylhexanoate, 2,2-methylene-bis-(2H-benzotriazole-2-yl)4-(tetramethyl-butyl)1,1,3,3-phenol, and 2-hydroxy-4-(methacryloyloxy)benzophenone; The coupling agent is one or more of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, 3-(2,3-epoxypropoxy)propyl trimethoxy silane, and γ-aminopropyl triethoxy silane; The mass ratio of the inorganic anti-ultraviolet material, the coupling agent and the organic ultraviolet absorber is (50-60): (0.1-2): (40-50), and can be specifically 56:1:43.
[0011] In the above-mentioned organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, the preparation method of the organic / inorganic composite anti-ultraviolet nanomaterial comprises the following steps: the inorganic anti-ultraviolet material, the coupling agent and the organic ultraviolet absorber react in an organic solvent to obtain the organic / inorganic composite anti-ultraviolet nanomaterial; preferably, the reaction temperature is 40-100°C, the time is 3-8 hours, such as reacting at 50°C for 6 hours; preferably, the organic solvent is one of toluene, ethanol and acetone. Among them, the method further comprises the following steps after the reaction is completed: centrifuge the system after the reaction to take out the precipitate, wash the precipitate with water and alcohol three times in sequence, and dry it in a vacuum oven at 105°C for 12 hours.
[0012] In the above organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, the dispersant is selected from one or more of polyamide-amine dendritic polymer, white oil, calcium stearate, N,N'-ethylene bisstearamide (EBS, wax powder), ethylene acrylic acid copolymer and maleic anhydride graft. As an example, the polyamide-amine dendritic polymer is dendritic polyamide amine G3 (PAMAM), brand CYD-130H.
[0013] In a second aspect, the present invention provides a method for preparing the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch as described in any one of the above items, comprising the following steps: adding the organic / inorganic composite anti-ultraviolet nanomaterial, the fluorescent brightener and the dispersant to the polyamide 66 resin and mixing them, and obtaining the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch by melt blending and extrusion.
[0014] In the above-mentioned method for preparing the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, in the mixing step, the mixing speed is 1000-3000 r / min (such as 2000 r / min), and the mixing time is 20-40 min (such as 30 min); In the melt-blending extrusion step, the melt-extrusion temperature is 220-270° C., and the mixing extrusion speed is 200-400 r / min (eg, 300 r / min).
[0015] In a third aspect, the present invention provides a functional fiber, comprising polyamide 66 fiber and any one of the above-mentioned organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatches.
[0016] In a fourth aspect, the present invention provides a method for preparing the functional fiber, comprising the following steps: vacuum drying the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch and polyamide 66 chips described in any one of the above items, mixing them, and then spinning them to form the functional fiber.
[0017] In the above-mentioned method for preparing functional fibers, the process conditions of the vacuum drying treatment are as follows: the vacuum degree is stabilized at 0.05-0.1 MPa, the temperature is 120°C, and the temperature is kept for 16-20 hours (such as 20 hours); In the spinning step, the processing temperature of the spinning machine screw and the box is 260-290° C., the drafting multiple is 0-3.5 times (such as 2 times), and the winding speed is 3800-4200 m / min (such as 4000 m / min).
[0018] The present invention has the following beneficial effects: (1) The polyamide 66 masterbatch with ultraviolet shielding function prepared by the present invention has the functions and characteristics of sun protection, heat insulation, safety, environmental protection, health and comfort, and has become the preferred fabric for high-end clothing and accessories.
[0019] (2) The preparation method of the organic-inorganic composite polyamide 66 masterbatch with anti-ultraviolet function of the present invention is to add organic anti-ultraviolet absorber and inorganic anti-ultraviolet absorber, fluorescent brightener and dispersant during the process of melt blending and extrusion of polyamide 66 resin. Organic / inorganic composite anti-ultraviolet nanomaterials can reflect, scatter and absorb ultraviolet rays, shield ultraviolet rays to the greatest extent; can protect resin from damage by ultraviolet rays, and protect human skin. In addition, the application of organic-inorganic composite particles can optimize the thermal stability and easy migration performance of organic compounds, while improving the dispersibility and compatibility of inorganic particles; highly branched and a large number of surface functional groups and three-dimensional cavity structure dispersant polyamide-amine dendrimer polymers are preferred, which can further improve the dispersion and processing performance of nanomaterials and improve the affinity between nanomaterials and polyamide resins; the addition of appropriate fluorescent brighteners can improve and adjust the color and gloss of fibers, which is beneficial to the subsequent dyeing and application of fibers.
[0020] (3) The polyamide 66 masterbatch produced by the present invention is processed by POY-DTY / FDY spinning technology to produce polyamide 66 fiber with excellent performance and anti-ultraviolet protection function. The fiber can be processed into high-end clothing or apparel materials with soft luster, soft feel and comfort, good air permeability, wear resistance, easy rinsing, anti-ultraviolet and care functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention provides a flow chart for preparing organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch and functional fiber. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0023] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0024] Example 1 This embodiment provides an organic / inorganic composite anti-ultraviolet matting polyamide 66 fiber masterbatch, the specific formula is as follows: 60 parts of polyamide 66 resin matrix; 35 parts of organic / inorganic composite anti-ultraviolet nanopowder; 2.0 parts of fluorescent brightener; 3.0 parts of dispersant; Among them, Figure 1 As shown in the figure, the preparation steps of the organic / inorganic composite anti-ultraviolet nanomaterial powder are as follows: the inorganic anti-ultraviolet material (cerium dioxide, 400 nm) is dispersed in the organic solvent ethanol, wherein 100 g of the inorganic anti-ultraviolet material is dispersed in 100 mL of ethanol, ultrasonically dispersed for 60 min, heated and stirred at 50°C, and then a coupling agent (isopropyl tri(dioctyl pyrophosphate acyloxy) titanate) and an organic ultraviolet absorber (2-hydroxy-4-(methacryloyloxy) benzophenone) are added respectively, wherein the mass ratio of the inorganic anti-ultraviolet material, the coupling agent and the organic ultraviolet absorber is 56:1:43. After reacting for 6 h, the precipitate is taken out by centrifugation, and the precipitate is washed with water and alcohol for 3 times in sequence, and then dried in a vacuum oven at 105°C for 12 h, and finally ground to obtain the organic / inorganic composite anti-ultraviolet nanomaterial.
[0025] This embodiment provides a method for preparing an organic / inorganic composite anti-ultraviolet extinction polyamide 66 fiber masterbatch, such as Figure 1 As shown, the specific preparation steps are as follows: in the process of melt blending and extrusion of polyamide 66 resin, organic / inorganic composite anti-ultraviolet nanomaterials, fluorescent whitening agent (2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene) and dispersant (wax powder, EBS, N,N'-ethylenebisstearamide) are added to obtain organic / inorganic composite anti-ultraviolet extinction polyamide 66 fiber masterbatch. In the melt blending and extrusion step, the mixing speed is 2000 r / min and the mixing time is 30 min; the melt extrusion temperature is 220-270 °C, and the mixing extrusion speed is 300 r / min.
[0026] Example 2 This embodiment provides an organic / inorganic composite anti-ultraviolet matting polyamide 66 fiber masterbatch, the specific formula is as follows: 50 parts of polyamide 66 resin matrix; 40 parts of organic / inorganic composite anti-ultraviolet nanopowder; 5.0 parts of fluorescent whitening agent; Dispersant 5.0 parts; The steps for preparing the organic / inorganic composite anti-ultraviolet nanomaterial powder are the same as those in Example 1.
[0027] The preparation method of the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch is the same as that in Example 1.
[0028] Example 3 This embodiment provides an organic / inorganic composite anti-ultraviolet matting polyamide 66 fiber masterbatch, the specific formula is as follows: 76 parts of polyamide 66 resin matrix; 20 parts of organic / inorganic composite anti-ultraviolet nanopowder; 1.5 parts of fluorescent brightener; 2.5 parts of dispersant; The steps for preparing the organic / inorganic composite anti-ultraviolet nanomaterial powder are the same as those in Example 1.
[0029] The preparation method of the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch is the same as that in Example 1.
[0030] Example 4 Compared with Example 1, the dispersant in Example 4 is replaced by dendritic polyamidoamine G3 (PAMAM), brand CYD-130H, and the remaining steps and conditions are the same as in Example 1.
[0031] The specific formula of polyamide 66 fiber masterbatch in this comparative example is as follows: Polyamide 66 matrix 60 parts; 35 parts of organic / inorganic anti-ultraviolet nanopowder; Brightener 2.0 parts; Dispersant 3.0 parts.
[0032] Comparative Example 1 Compared with Example 1, the masterbatch formula in Comparative Example 1 uses inorganic anti-ultraviolet nanomaterials (cerium dioxide, 400 nm), and does not use organic / inorganic composite anti-ultraviolet nanopowders. The remaining steps and conditions are the same as those in Example 1.
[0033] The specific formula of polyamide 66 fiber masterbatch in this comparative example is as follows: Polyamide 66 matrix 60 parts; 35 parts of inorganic anti-ultraviolet nano powder; Brightener 2.0 parts; 3.0 parts of dispersant; Comparative Example 2 Compared with Example 1, the masterbatch formula in Comparative Example 2 uses an organic anti-ultraviolet agent (2-hydroxy-4-(methacryloyloxy) benzophenone), and does not use an organic / inorganic composite anti-ultraviolet nanopowder. The remaining steps and conditions are the same as those in Example 1.
[0034] The specific formula of polyamide 66 fiber masterbatch in this comparative example is as follows: Polyamide 66 matrix 60 parts; 35 parts of organic anti-ultraviolet agent; Brightener 2.0 parts; 3.0 parts of dispersant; Comparative Example 3 Compared with Example 1, no brightener was added in Comparative Example 3, and the remaining steps and conditions were the same as those in Example 1.
[0035] Performance Testing The functional masterbatch in the above embodiment and comparative example is made into functional fiber by masterbatch blending modification technology, and the preparation steps are as follows: UV-resistant polyamide 66 fiber masterbatch and polyamide 66 chips (mass ratio is 95:5) are vacuum dried and mixed, and then spun to form functional fibers; the process conditions of vacuum drying of chips are as follows: vacuum degree is stable at 0.05-0.1 MPa, temperature is 120 ℃, and heat preservation is 20 h; the processing temperature of the spinning machine screw and box is 260-290 ℃, the drafting multiple is 2, and the winding speed is 4000 m / min.
[0036] (1) Anti-ultraviolet fiber gloss According to the standard GB / T 17644-2008 “Test method for whiteness and chromaticity of textile fibers”, the whiteness of the fibers prepared from the masterbatches of Example 1 and Comparative Example 3 was tested.
[0037] Through the L value, we can clearly compare the whiteness of the fibers prepared by the masterbatch of Example 1 and Comparative Example 3. The L value of Comparative Example 3 is 89, which is significantly lower, while the L value of Example 1 is 99, which has a higher whiteness. It can be seen from the comparison that the addition of fluorescent whitening agent can improve the whiteness of the fiber.
[0038] (2) Performance indicators of UV-resistant fibers The ultraviolet protection value (UPF) and mechanical properties (breaking strength and breaking elongation) of the ultraviolet resistant polyester fiber prepared above were tested. The ultraviolet protection value test procedure was referred to "GB / T 18830-2009", and the mechanical property test procedure was referred to "GB / T14344-2008". The test results are shown in Table 1; Table 1 Performance test table of Examples 1-4 and Comparative Examples 1-3
[0039] As shown in Table 1, the UPF values of Examples 1 to 4 are significantly higher than those of Comparative Examples 1 and 2. From the above results, it can be seen that the use of the organic / inorganic composite anti-ultraviolet nanomaterials provided by the present application can significantly improve the anti-ultraviolet performance of polyamide fibers, and the anti-ultraviolet performance of the composite anti-ultraviolet nanomaterials is higher than that of a simple combination of single organic or inorganic anti-ultraviolet materials; in addition, from the mechanical property results of Examples 1 to 4 and Comparative Examples 1 and 2, it can be obtained that the mechanical properties of the composite anti-ultraviolet nanomaterials are higher than those of a simple combination of single anti-ultraviolet materials. The reason for the above results is that compared with the addition of composite anti-ultraviolet nanomaterials, the concentrations of inorganic nanomaterials and organic ultraviolet absorbers added separately are significantly higher, and the thermal stability of organic single molecules is poor; the effective volume of organic or inorganic single molecules is small and easy to self-aggregate, resulting in their dispersion effect in the polyamide matrix being lower than that of the composite anti-ultraviolet nanomaterial in the polyamide matrix, thereby affecting the mechanical properties and anti-ultraviolet performance of the masterbatch. In addition, from the comparison results of Example 1 and Example 4, it can be concluded that the dispersant plays a key role in the dispersion of the anti-UV nanopowder in the polyamide masterbatch and the fiber. The polyamide-amine dendritic polymer dispersant with a highly branched structure, a large number of surface functional groups and a three-dimensional cavity structure improves the affinity of the composite anti-UV powder and the polyamide matrix, improves the uniform dispersion of the anti-UV powder, and improves the mechanical properties and anti-UV properties of the fiber. The dispersant in the present invention is preferably a polyamide-amine dendritic polymer.
[0040] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.
Claims
1. An organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch, characterized in that: In parts by weight, it is made from the following raw materials: 50-85 parts of polyamide 66 resin; 10-45 parts of organic / inorganic composite anti-ultraviolet nanomaterials; 0.5-10 parts of fluorescent whitening agent; Dispersant 0.2-5.0 parts; The organic / inorganic composite anti-ultraviolet nano material is made of an inorganic anti-ultraviolet material, a coupling agent and an organic ultraviolet absorber.
2. The organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch according to claim 1, characterized in that: The fluorescent brightener is selected from one or more of 3-(4-chlorophenyl)-1-(4-phenylsulfonic acid) pyrazoline, 2,5-bis(5-tert-butyl-2-benzoxazolyl) thiophene, and 4-(2-benzoxazolyl)-4'-(5-methyl-2-benzoxazolyl) diphenylethylene.
3. An organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch according to any one of claims 1-2, characterized in that: The inorganic anti-ultraviolet material is selected from one or more of titanium dioxide, cerium dioxide, and zinc dioxide, and has a particle size of 100 to 800 nm; The organic ultraviolet absorber is selected from one or more of 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazine-4-one, 2-[4-(4,6-diphenyl-1,3,5-triazine-2-yl)-3-hydroxyphenoxy]ethyl-2-ethylhexanoate, 2,2-methylene-bis-(2H-benzotriazole-2-yl)4-(tetramethyl-butyl)1,1,3,3-phenol, and 2-hydroxy-4-(methacryloyloxy)benzophenone; The coupling agent is one or more of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, 3-(2,3-epoxypropoxy)propyl trimethoxy silane, and γ-aminopropyl triethoxy silane; The mass ratio of the inorganic anti-ultraviolet material, the coupling agent and the organic ultraviolet absorber is (50-60): (0.1-2): (40-50).
4. An organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch according to any one of claims 1 to 3, characterized in that: The preparation method of the organic / inorganic composite anti-ultraviolet nanomaterial comprises the following steps: the inorganic anti-ultraviolet material, the coupling agent and the organic ultraviolet absorber react in an organic solvent to obtain the organic / inorganic composite anti-ultraviolet nanomaterial; preferably, the reaction temperature is 40 to 100° C. and the reaction time is 3 to 8 h; preferably, the organic solvent is one of toluene, ethanol and acetone.
5. An organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch according to any one of claims 1 to 4, characterized in that: The dispersant is selected from one or more of polyamide-amine dendrimer, white oil, calcium stearate, N,N'-ethylenebisstearamide, ethylene acrylic acid copolymer and maleic anhydride grafted product.
6. The method for preparing the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch according to any one of claims 1 to 5 comprises the following steps: adding the organic / inorganic composite anti-ultraviolet nanomaterial, the fluorescent brightener and the dispersant to polyamide 66 resin and mixing them, and obtaining the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch by melt blending and extrusion.
7. The method for preparing the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch according to claim 6, characterized in that: In the mixing step, the mixing speed is 1000-3000 r / min, and the mixing time is 20-40 min; In the melt blending and extrusion step, the melt extrusion temperature is 220-270° C., and the mixing and extrusion speed is 200-400 r / min.
8. A functional fiber, characterized in that: The invention comprises polyamide 66 fiber and the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch described in any one of claims 1 to 5.
9. The method for preparing the functional fiber according to claim 8, characterized in that: The method comprises the following steps: vacuum drying the organic / inorganic composite anti-ultraviolet polyamide 66 fiber masterbatch and polyamide 66 chips described in any one of claims 1 to 5, mixing them evenly, and then spinning them into the functional fiber.
10. The method for preparing functional fiber according to claim 9, characterized in that: The process conditions of the vacuum drying treatment are as follows: the vacuum degree is stabilized at 0.05-0.1 MPa, the temperature is 120°C, and the temperature is kept for 16-20 hours; In the spinning step, the processing temperature of the spinning machine screw and the box is 260-290° C., the drafting multiple is 0-3.5 times, and the winding speed is 3800-4200 m / min.
Citation Information
Cited By
Anti-ultraviolet textile material and preparation method thereof
CN119913633A
High-wear-resistance polyamide fiber and preparation method thereof
CN121065844A